Molecular dynamic study of MlaC protein in Gram‐negative bacteria: conformational flexibility, solvent effect and protein‐phospholipid binding. (14th May 2016) - Huang, Yu‐ming M.; Miao, Yinglong; Munguia, Jason; Lin, Leo; Nizet, Victor; McCammon, J. Andrew
Abstract: The composition of the outer membrane in Gram‐negative bacteria is asymmetric, with the lipopolysaccharides found in the outer leaflet and phospholipids in the inner leaflet. The MlaC protein transfers phospholipids from the outer to inner membrane to maintain such lipid asymmetry in the Mla pathway. In this work, we have performed molecular dynamics simulations on apo and phospholipid‐bound systems to study the dynamical properties of MlaC. Our simulations show that the phospholipid forms hydrophobic interactions with the protein. Residues surrounding the entrance of the binding site exhibit correlated motions to control the site opening and closing. Lipid binding leads to increase of the binding pocket volume and precludes entry of the water molecules. However, in the absence of the phospholipid, water molecules can freely move in and out of the binding site when the pocket is open. Dehydration occurs when the pocket closes. This study provides dynamic information of the MlaC protein and may facilitate the design of antibiotics against the Mla pathway of Gram‐negative bacteria.